EXCEL ЭЛЕКТРОН КЕСТЕ ПРОГРАММАСЫНДА СЫЗЫҚЛЫ ПРОГРАММАЛАСТЫРЫЎ МӘСЕЛЕЛЕРИН СИМПЛЕКС УСЫЛЫ МЕНЕН ШЕШИЎ - Жалелов, Р.М.; Жалелов K.М. (FAN va JAMIYAT, 2020)
The article deals with the statement of a problem of linear programming and its decision with the help of a simplex method. Here it is presented the sequence of the decision of a problem and results of calculations by means of program Excel.